Assessment of soil erosion risk in Chamchamal catchment using RUSLE integrated into GIS Techniques - Karim, Tariq Hama; Qadir, Kamal Sharif; Mohammed, Danya Omer (Sulaimani Journal for Pure and Applied Sciences, 2021)
In Iraqi Kurdistan Region, as in most Mediterranean countries, assessment of soil erosion risks is a challenging task mainly due to the non-availability or insufficiency of relevant data. In the current study, the soil erosion risks have been estimated by integrating the spatial data on potential erosion rates and soil loss tolerance limits for conservation planning at the sub-catchment level in Chamchamal district, Sulaimani, Iraqi Kurdistan Region. To achieve the above objectives, the study catchment was delineated with the support of GIS after obtaining the Dem of Chamchamal district. The remote sensing (RS) and a geographic information system (GIS) were used to estimate the spatial distribution of soil erosion across the Chamchamal district, to identify the risk of soil erosion, and to develop a conservation priority map. People can reach a common goal: to gain actionable intelligence from all types of data. Additionally, the study catchment was subdivided into 12 subcatchments using the same tool. The estimated annual soil loss for different subcatchments is characterized by a wide range of variations. It ranges from a minimum of 7.08 t ha-1 yr-1 at subcatchment 1 to as high as 252.31 t ha-1 yr-1 at sub-catchment 3. With a few exceptions, the soil tolerance limit at the investigated grid points was estimated at10 t ha-1 yr-1. The results also revealed that around 12% of the whole catchment has a negligible risk of soil erosion above the tolerance limits, and does not call for immediate soil conservation measures. The remaining area (454.96 km2) requires conservation planning with different prioritizations. Subcatchments 2, 3, 7, and 10 were identified as the worst affected districts in terms of soil erosion and therefore require immediate attention of natural resources. The weighted soil erosion risk index (WSERI) categorized sub-catchments 2, 3, 7, and 10 as being of topmost priority as it is the most severely affected areas. The recommended measures to conserve soil and water encompassed three broad categories, namely, vegetative, soil, and mechanical measures. Within the same sub-catchment, one or a combination of several measures can be implemented based on the nature and intensity of the problem.
Keywords: Annual soil loss; RUSLE-variables; soil loss tolerance; WSER index; soil erosion RS; GIS